Free vibration analysis of porous functionally graded piezoelectric microplates resting on an elastic medium subjected to electric voltages - Wu, C.-P.; Lin, E.-L. (Archives of Mechanics, 2022)
Basing on the consistent couple stress theory (CCST), we develop a unified size-dependent shear deformation theory to analyze the free vibration characteristics of simply supported, porous functionally graded (FG) piezoelectric microplates which resting on the Winkler–Pasternak foundation are subjected to electric voltages. Various CCST-based shear deformation theories can be reproduced by incorporating their corresponding shape functions, which characterize the through-thickness distributions of the shear deformations, into the unified size-dependent theory. The reproduced CCST-based plate theories include the classical plate theory (CPT), the first-order shear deformation plate theory (SDPT), Reddy’s refined SDPT, the sinusoidal SDPT, the exponential SDPT, and the hyperbolic SDPT. The unified size-dependent theory is subsequently used to determine the natural frequencies of simply supported, porous FG piezoelectric microplates and their corresponding vibration mode shapes. The effects of the material length scale parameter, the length-to-thickness ratio, the material-property gradient index, different values of the applied voltages, the porosity parameter, different porosity distribution patterns, the Winkler spring coefficient, and the shear modulus of the surrounding medium on the natural frequencies of the porous FG piezoelectric microplates are examined and appear to be significant.